Marine debris in tourism area of Dodola Island Beach, Morotai Island District - Sukarmin Idrus; Marwis Aswan; Sudin Sumahi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Coastal and marine areas are very vulnerable to various pollution threats from human domestic activities (marine debris), industry (fishery management) and other activities. One of the the problems faced in the management of Dodola island tourism was marine debris. This study aims to determine the composition of marine debris generated from tourism activities. Futhermore this study was necessary as basic information to formulate appropriate strategies in managing marine debris. This research was conducted from August to September 2021. Observations were made by visual observation at porposive area. Analysis of the type and weight taken from the observed waste such as the number of pieces, weight, composition and density of solid waste and separated according to the type of organic and inorganic. This result showed inorganic waste such as plastic bottles and cups, plastic packages, Styrofoam, sandals/shoes, glass bottles, diapers, cardboard and aluminum cans with a total of 664 items or 58% pieces, while for organic waste consisting of wood, bamboo, coconut and nipa fruit and banana leaves, with the number of pieces as much as 473 items or 42%. Organic waste has a weight of 203,422 grams or 85% and organic marine waste is 35,915 grams or 15%. The types of organic waste with the highest and heaviest amounts were bamboo 70.51% and 73.77%. Meanwhile, the type of inorganic waste with the highest amount was plastic bottles/cups 79.17% and the heaviest type of waste was glass bottles 55.08%.Keywords:Marine debrisGPSOrganicInorganic